Drivers of Green Purchase Intention: The Role of Green Marketing, Brand Image, Perceived Value, and CSR in Uniqlo Indonesia - Simbolon, Valentina Lauretta Prameswari; Salim, Lina (STIE Pelita Nusantara Semarang, 2026)
The fashion industry’s waste problem has become one of the growing environmental issues in Indonesia. Sustainability programs have emerged as an alternative solution for fashion industry players, including UNIQLO, which has implemented sustainable production practices and clothing waste management initiatives. This study aims to analyze the influence of green marketing, green brand image, green perceived value, and corporate social responsibility on green purchase intention, with UNIQLO as the research object. This study used primary data obtained through non-probability sampling and purposive sampling techniques. A total of 290 respondents were collected as sample, with criteria of being 17–50 years old, residing Jabodetabek area, and being familiar with the UNIQLO brand. Primary data were gathered through an online questionnaire. The results show that 3 hypotheses were accepted and 1 hypothesis was rejected. Green marketing, green perceived value, and corporate social responsibility have a positive and significant influence on green purchase intention, while green brand image has no effect to green purchase intention toward UNIQLO brand.